Penerapan Metode Eksprimen untuk Meningkatan Hasil Belajar Biologi Siswa SMK Analis Kesehatan Jember - Wahyuningsih, Sri (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2020)
Experimental method was the one of the factors that affect student learning outcomes as well as play an important role in supporting the success of teaching biology class. This aim of this study was to determine the learning outcome and completeness of biology learning outcomes of SMK Analis Kesehatan Jember students in particular of XB class on animal tissue learning. This research was used the Class Room Action Research and conducted in two cycles. The results showed that the average value XB graders Pre cycle is 70.30. After doing research experiments, obtained an average yield value in the first cycle was 77, 56 and 82.56 on the second cycle. The completeness of learning results of students in pre-cycle actions only amounted of 62.16%. The result after the research with an experimental method in the first cycle showed completeness of 86.48% and 94.59% in the second cycle.